ANALISA PENGUJIAN KETAHANAN BEJANA TEKAN DENGAN METODE HIDROSTATICTEST - TB. U. Adi Subekhi; Jatira; Budi Siswanto (Jurnal Teknologika, 2024)
A pressure vessel is a place or container for storing or building fluids, both in the form of liquids and gases as one of the process tools used in industry, especially in the chemical, petroleum, and electricity generation industries with steam separators which are very important components in electricity generation. The steam separator is used to separate the fluid in the liquid phase and gas phase (steam or steam) to produce a higher level of dryness and more contained in the steam that will be used to turn the turbine. Based on the ASME VIII standard in 2010 which was a vessel before it could be used in payment and one type of testing was by hydrostatic test method. From the calculation of the voltage that occurs when hydrostatic administration is 5.037 MPa (50.37 Bar), the force that divides the locked flange 8 bolts M-16 x 2.0 (P), with the introduced voltage (τ) inside the pressure vessel, at what is permitted τ (that occurs (40 N / mm2 ≥ 36 40 N / mm2. from the test results using hydrostatic test methods obtained for hydrostatic testing can determine leakage and test with 1.5 x work work (30 bar) steam separator pressure vessel no defects appear, crank on the weld or deformation occurs. Key words: Hydrostatic, Pressure vessel, Steam Separator.